Hubungan Penyakit Infeksi Ibu dengan Kejadian BBLR - Zakiah, Nur; Novi Aryanti; Nurul Annisa; Abdul Fandir (Universitas Sulawesi Barat, 2025)
One of the indicators of a country’s success in improving public health is the reduction in infant mortality rates (IMR). One of the main contributors to the high IMR is Low Birth Weight (LBW). Babies born with LBW tend to experience cognitive developmental disorders, mental retardation, and are more prone to infections that can lead to illness or even death.This study aims to examine the extent to which one of the factors causing low birth weight, namely maternal infectious diseases, is associated with LBW incidence. The research was conducted in Majene Regency, specifically in the East Banggae and Banggae subdistricts. This study employed a cross-sectional design with an accidental sampling method involving 80 respondents. In this study, we observed symptoms of infections such as sore throat, nasal congestion, fever, and cough lasting less than two weeks. Statistical analysis revealed that none of the variables were significant (p-value > 0.05). It is important to conduct further research on the relationship between maternal infectious diseases and LBW, focusing on different study locations. Keyword : Low Birth Weihgt, Infection, Mother, Infant.